KARDIOCHIRURGIA DOROSŁYCHCardiac myxoma: 10 years’ experience in 29 patients operated on with crystalloid cardioplegia – short- and long-term results - Rachwalik, Maciej; Obremska, Marta; Goździk, Anna; Nowicki, Rafał; Bielicki, Grzegorz; Jakubaszko, Jacek; Dumański, Andrzej; Pelczar, Marek; Stachurski, Andrzej; Oczko, Janusz; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background: Cardiac myxoma is generally considered to be a surgical emergency. Cardiac myxomas were resected in 29 patients. Material and methods: Patient data and data obtained during follow-up from the 10-year period 1999-2008 of the survivors were reviewed. The tumour was always removed within 24 hours of admission. Results: Early survival was 100%. Long-term results were collected from a group of 27 patients and all of them were symptom-free. Most cases of cardiac myxoma observed over the last decade correspond to stable forms. Conclusions: Myxoma is usually observed in the older and higher risk population, often at an early stage. Surgical excision of atrial myxoma gives excellent short-term and long-term results leading to an eventual cure of non-familial myxomas. However, familial myxomas retain a strong tendency to recur even 20 years after excision.